Validation of rapid velocity encoded cine imaging of a dynamically complex flow field using turbo block regional interpolation scheme for k space - Kortright, Eduardo; Doyle, Mark W.; Anayiotos, Andreas (My University, 2001)
A study on block regional interpolation scheme for k space (BRISK) magnetic resonance imaging (MRI) velocity encode cine (VEC) demonstrates that these complex flow fields can be performed with minimal loss of information while remaining well within clinically acceptable scan durations. Compared to conventional MRI, Turbo BRISK represented the complex throughplane flow with excellent accuracy in as little as 6% of the conventional scan time. At conventional resolutions, Turbo BRISK was proven as a promising tool for the eventual clinical evaluation of complex intravascular flows of non-unidirectional character. In addition, it should make three-dimensional flow imaging in humans possible.
Keywords: k-spaces; Hemodynamics; Cardiovascular system--Diseases; Computer simulation